Strategic Location of Traditional Markets in Medan City: (A Spatial and Economic Approach) - Olivia Maria Margaretha Panjaitan; Feby Milanie; Ruth Riah Ate Tarigan (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Traditional markets play a central role in the local economic system and the social life of communities, particularly in Medan City. However, the dynamics of urbanization, competition from modern retail, and changes in consumer behavior have posed significant challenges to their sustainability. This study aims to analyze the relationship between the strategic location of traditional markets and their economic performance using a mixed-methods approach and spatial analysis. The research focuses on six traditional markets in Medan City: Petisah Market, Sukaramai Market, Beruang Market, Ikan Lama Market, Sei Sikambing Market, and Pringgan Market. Quantitative data were collected through questionnaires using a Likert scale and analyzed descriptively and correlationally, while qualitative data were gathered through field observations and in-depth interviews to interpret the socio-spatial context of each market. The key variables include accessibility, commodity diversity, and environmental comfort, which are linked to economic performance indicators such as visitor numbers, buyer loyalty, and sales stability. The results show that Petisah, Pringgan, and Ikan Lama Markets scored highest in these variables and demonstrated better economic performance. Correlation analysis identified commodity diversity as the most influential factor on economic performance, followed by environmental quality and accessibility. To strengthen the analysis, a SWOT model was also applied to identify the strengths, weaknesses, opportunities, and threats faced by traditional markets. This analysis reveals that the primary strengths of the markets lie in their location and social interaction, while the main challenges stem from a lack of modern management and pressure from digital markets. This study recommends development strategies based on local advantages, infrastructure modernization, market information digitalization, and cultural promotion as steps to sustainably enhance the competitiveness of traditional markets amid urban spatial changes.